An improved pore‐scale biofilm model and comparison with a microfluidic flow cell experiment. Issue 12 (13th December 2013) - Tang, Youneng; Valocchi, Albert J.; Werth, Charles J.; Liu, Haihu
<x xml:space="preserve">Abstract</x> [1] This work presents a pore‐scale biofilm model that solves the flow field using the lattice Boltzmann method, the concentration field of chemical species using the finite difference method, and biofilm development using the cellular automaton method. We adapt the model from a previous work and expand it by implementing biofilm shrinkage in the cellular automaton method. The new pore‐scale biofilm model is then evaluated against a previously published pore‐scale biofilm experiment, in which two microfluidic flow cells, one with a homogeneous pore network and the other with an aggregate pore network, were tested for aerobic degradation of a herbicide. The simulated biofilm distribution and morphology, biomass accumulation, and contaminant removal are generally consistent with the experimental data. Biofilm detachment in this model occurs when the local shear stress is above a critical value. We use the critical value from our previously published modeling study and find it works well in this case, even though we now have a different pore network and a different microbial species. We also use the model to show that the interaction between flow and biofilm growth is important to predict contaminant removal. The computational time of the new model is reduced 90% compared to our prior work due to implementation of biofilm shrinkage in the cellular automaton method. To the best of our knowledge, this is the first time that biofilm shrinkage has been incorporated into a pore‐scale model for simulation of pollutant biodegradation in porous media.